Microgravity for detecting cavities in an archaeological site in Sardinia (Italy). Issue 5 (1st June 2015) - Fais, S.; Radogna, P.V.; Romoli, E.; Matta, P.; Klingele, E.E.
ABSTRACT: We present a microgravity study over an archaeological site in Sardinia (Italy) subject to local subsidence, which could be correlated with subterranean cavities. Taking into account the local geological conditions and other factors such as topography, the high urbanization of the area, and financial factors, the micro‐gravity method was used to determine the presence of voids and whether these voids are correlated with the local subsidence. A complete Bouguer anomaly map was produced with topography corrections with a density of 1.80  g / cm 3 . The density used for the corrections was determined in the laboratory on samples of the geological formations from the same area. The gravity anomaly has been further corrected for the effect of massive structures such as walls and isolated blocks. After removing a third‐order polynomial regional trend, the residual anomaly shows small but well‐identified anomalies of circular shapes with amplitudes between 15  μGal and 40  μGal . The anomalies are spatially well correlated with the local subsidence, and a map of the vertical gradient of the residual field shows peaks located exactly over the small anomalies previously cited. Using two‐dimensional qualitative and quantitative modelling, it is possible to assume that the voids are the cause of the anomalies and therefore could be also the cause of the local subsidence.